GEREJA RAMAH DISABILITAS SEBAGAI RUANG PENDIDIKAN INKLUSIF - Frigen Rinaldy Lay; Diani Jumentri Kabnani, Febrida Bani, Ferida Jelianti Liunokas, Harley Sandra Taebenu, Ivon Stessy S (Adisam Publisher, 2026)
This article discusses the importance of disability-friendly churches as inclusive educational spaces capable of reaching everyone, including children with special needs, in church life. This study employs a qualitative method, specifically a literature review, by examining various relevant journal articles on this topic. The results of the study indicate that the church bears moral, spiritual, and social responsibilities to serve as an ecosystem capable of welcoming every child without discrimination. Theological foundations regarding God’s love, the dignity of humanity as the image of God, and the example of Jesus’ ministry to the marginalized or those on the fringes of society form the very foundation for building an inclusive or disability-friendly church ministry. The reality on the ground shows that children with disabilities still face stigma, limited access to services, and a lack of attention to their growing faith education needs. Given this, the church should provide adaptive and down-to-earth ministries through an inclusive curriculum, pastoral care, training for church leaders, and fostering the involvement of parents and the wider community. A disability-friendly church is not merely an expression of social concern but an integral part of the tangible manifestation of Christ’s love, which embraces all children as precious individuals regardless of their background.